Source Transformation for MATLAB Automatic Differentiation. - Kharche, Rahul V.; Forth, Shaun A. (Springer, 2005)
We present MSAD, a source transformation implementation of forward mode automatic differentiation for MATLAB. MSAD specialises and inlines operations from the fmad and derivvec classes of the MAD package. The operator overloading overheads inherent in MAD are eliminated while preserving the derivvec class's optimised derivative combination operations. Compared to MAD, results from several test cases demonstrate significant improvement in efficiency across all problem sizes.